SYNTHESIS OF POLYDIACETYLENE BY MICROWAVE-ASSISTED FOR SURFACTANT DETECTION APPLICATION IN THE ENVIRONMENT - Khanantong, Chanita; Srinopkun, Thanutpon (Life Sciences and Environment Journal, 2024)
This research focuses on the synthesis of polydiacetylene (PDA) solutions using microwave-assisted method for detecting surfactant contamination in the environment. The PDA was prepared through the solution-mixing method (SMM) combined with microwave synthesis at 80°C, using 1000 watts of power for varying durations of 5, 15, 30, and 60 minutes. It was observed that a high-concentration solution with clear morphology was achieved within just 5 minutes of microwave exposure. The exposure time significantly impacted the crystalline structure and molecular interactions, as analyzed by XRD and FT-IR, in alignment with the thin-film hydration method (TFHM). The microwave-assisted SMM simplified the synthesis process and enhanced safety by eliminating the need for volatile chemical evaporation during fabrication. Additionally, the study examined the colorimetric response of PDA to the cationic surfactant CTAB. The concentration of CTAB that induced a clear color change from blue to yellow was 0.22, 0.45, 0.67, and 1.12 mg/L for synthesis times of 5, 15, 30, and 60 minutes, respectively. The results indicate that shorter synthesis times lead to faster color transitions. This study provides valuable insights into the application of microwave-assisted PDA synthesis for monitoring surfactant contamination in the environment.